Role of Collagen in Gaping of Fish Fillets - Hassan, Femeena; George, Sajan; M.K., Mukundan; P.M., Sherief (Fishery Technology, 2025)
The extent of gaping in the skinless fillets of Sardinella longiceps, Rastrelliger kanagurta, Oreochromis mossambicus, Cyprinus carpio, Euthinnus affinis and Scoliodon sorrkozvah during frozen storage and its relationship with the collagen content of the muscle were studied. Gaping was not significant in any of the fillets during the first three months of frozen storage, irrespective of the collagen content. Significant gaping occurred in fish stored for longer period. The degree of gaping was more in those fish which had low collagen content. Removal of skin appeared to be helpful in preventing gaping.